Contingent Valuation in Measuring Fishermen’s Willingness to Pay for the Conservation of Hammerhead Shark (Sphyrna spp) Resources in Tanjung Luar, East Lombok - Karto Wongsopatty; Luky Adrianto; Zairion Zairion; Irfan Yulianto; Hollie Booth; Andi Zulfikar (Faculty of Fisheries and Marine Science, Brawijaya University, 2022)
The hammerhead shark has high economic value, but its population is highly threatened due to its high exploitation. This study aims to calculate the level of preference of shark fishermen on the value of willingness to pay for the conservation of hammerhead shark resources. This research was conducted from November to December 2020 in Tanjung Luar Village, East Lombok Regency. The method used is observation and in-depth interviews with a sample of 150 shark fishermen. The analysis used is binary logit regression analysis using the R studio 4.1.2 tool. The results of this study indicate that (1) the total price of willingness to pay from all Tanjung Luar shark fishermen is IDR 9,654,000, and the average monthly value is IDR 53,633 per person; (2) factors that are quite influential on respondents' willingness to pay are age, education level, number of family members, and monthly income. The conservation of hammerhead shark resources needs to be considered because it has been included in the CITES Appendix II red list with a critically endangered status towards extinction. Suggestion there is a need for educational steps from various parties to fishermen regarding the importance of the existence of hammerhead sharks in the ecosystem so that they can reduce the high level of fishing activity in nature.